A Policy Response to Canadian Economic Inequality - Testart, Shannon M. (My University, 2012)
Economic inequality is increasing in Canada and throughout the world. In addition to the equity concerns of distributive justice, growing economic inequality negatively impacts poverty, social cohesion, and the stability of the economy. This master’s thesis undertakes a major literature review to explore the trends in economic inequality and the policies that influence it.
The current increase in economic inequality has been dominated by an increase in the income and wealth of the 1% to which the Occupy movement has drawn significant attention. Policies to directly counter this rise in both before- and after-tax top incomes are critical to combatting economic inequality. In addition to highlighting policies that target the very rich, this thesis examines intersections between traditional social policy and broader public policy in the field of economic inequality. It also argues for increased consideration of economics in social work research and policy practice. Economic inequality should be a concern to social workers alongside poverty.
Policies in four areas are considered: income taxes and transfers, public services, labour market institutions, and capital market interventions. Recommendations are made for the future. Addressing economic inequality through national policy is both possible and advantageous. A comprehensive policy package involving policies from the four areas explored has the potential to reduce economic inequality.
Keywords: income inequality; wealth inequality; redistribution; neoliberalism; maximum wage; Robin Hood Tax; Inequality and Stratification; Inequality and Stratification